ENT 530 Social media portfolio: Do’zee / Muhammad Haziq Ahmad Nazri - Ahmad Nazri, Muhammad Haziq (2021)
This assignment was done to hone my talents in online business. It is also to help my use of technology in business. To achieve the objectives of this project, I have been using the Facebook page to run an e-commerce business for several months. I find, the use of Facebook app is very effective for running an online business. This is because the use of the Facebook application is very easy to access by anyone. Facebook is also one of the most used applications in Malaysia. So my advertising or post on Facebook is easily spread and reaches many Facebook users. Websites like Canva also help me to create beautiful posters to grab the attention of users.